2020
DOI: 10.1021/acsomega.0c02392
|View full text |Cite
|
Sign up to set email alerts
|

Polystyrene-block-poly(ethylene oxide) Thin Films Fabricated from a Solvent Mixture for the Co-Assembly of Polymers and Proteins

Abstract: The co-assembly of peptides and proteins in poly(styrene- block -ethylene oxide) (PS- b -PEO) thin films has proven to be a promising method to fabricate polymer–biomolecule functional materials. Contrary to the covalent immobilization of biomolecules on surfaces, co-assembly presents the opportunity to arrange cargo within thin films, which can be released upon exposure to an aqueous environment. The use of a mixed solvent system ensures the solubilization of hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…Amphiphilic block copolymers like PS-b-PMMA and PS-b-PEO in nanoscale orders have attracted great interest in this field. [18][19][20] Selectively removing one block leads to nanoporous template which can be useful in an emerging class of applications ranging from microelectronic devices, masks for lithographic application, and semiconductors to filtration. 21,22 In general, Controlling the domain spacing is a current primary focus for these applications.…”
Section: Impacts Of Architecture and Microstructurementioning
confidence: 99%
See 1 more Smart Citation
“…Amphiphilic block copolymers like PS-b-PMMA and PS-b-PEO in nanoscale orders have attracted great interest in this field. [18][19][20] Selectively removing one block leads to nanoporous template which can be useful in an emerging class of applications ranging from microelectronic devices, masks for lithographic application, and semiconductors to filtration. 21,22 In general, Controlling the domain spacing is a current primary focus for these applications.…”
Section: Impacts Of Architecture and Microstructurementioning
confidence: 99%
“…Self‐assembly of block copolymers can produce orderly structures with atomic or molecular level precisions. Amphiphilic block copolymers like PS‐ b ‐PMMA and PS‐ b ‐PEO in nanoscale orders have attracted great interest in this field 18–20 . Selectively removing one block leads to nanoporous template which can be useful in an emerging class of applications ranging from microelectronic devices, masks for lithographic application, and semiconductors to filtration 21,22 .…”
Section: Impacts Of Architecture and Microstructurementioning
confidence: 99%
“…Our research group has previously studied and optimised the solvent composition of PS- b -PEO in a benzene/methanol/water (BMW) solvent mixture. 48 In short, the ideal solvent composition was 81/17.9/1.1 vol% BMW, with ratios further from this point either phase separating or producing films with defects. Additionally, our research group has also confirmed the ability of these films to remain microscopically undisturbed with the incorporation of moderate concentrations of biomolecules.…”
Section: Introductionmentioning
confidence: 99%
“…Polystyrene-block-poly-(ethylene oxide) (PS-b-PEO) has been utilized extensively for this biomolecule co-assembly. [46][47][48] Our research group has previously demonstrated the biocompatibility of PS-b-PEO thin films within cell culture in vitro. 49 Further, we have explicitly demonstrated the ability for proteins to localise within the PEO domains of PS-b-PEO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation